Maternal morbid obesity: financial implications of weight management. Issue 5 (4th October 2015) - Caldas, M. C.; Serrette, J. M.; Jain, S. K.; Makhlouf, M.; Olson, G. L.; McCormick, D. P.
Summary: The objective of this study was to evaluate health outcomes and costs of pregnancies complicated by extreme maternal obesity (class III obesity, body mass index ≥ 40). We conducted a retrospective case‐control descriptive study comparing extremely obese women (cases) and their infants with randomly selected controls. Health outcomes were obtained from the medical records and costs from billing data. Total costs for each mother–infant dyad were calculated. Compared with 85 controls, the 82 cases experienced higher morbidity, higher costs and prolonged hospital stay. However, 26% of cases maintained or lost weight during pregnancy, whereas none of the controls maintained or lost weight during pregnancy. When mother/infant dyads were compared on costs, case subjects who maintained or lost weight experienced lower costs than those who gained weight. Neonatal intensive care consumed 78% of total hospital costs for infants of the obese women who gained weight, but only 48% of costs for infants of obese women who maintained or lost weight. For extremely obese women, weight management during pregnancy was achievable, resulted in healthier neonatal outcomes and reduced perinatal healthcare costs.